PENERAPAN PERGERAKAN KAMERA DINAMIS PADA FILM PENDEK BUKAN SALAHKU DI CV LUAR KOTAK AUDIO VISUAL - I Putu Kevin Andika Prananda; I Kadek Puriartha; Made Rai Budaya Bumiarta (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
The film is a medium that uses moving images and sound to tell a story or convey a message to the audience. Films can be made in various genres, such as drama, comedy, action, horror, and so on, and can be watched in theaters or on platforms that provide streaming services. In addition, films can also be made in various formats, such as feature films or short films. Dynamic camera movement allows the camera to move during shooting to provide a more dynamic and interesting visual effect. This technique can be used for various purposes, such as following the action that is happening, providing a different perspective, or creating a certain atmosphere. Dynamic camera movements can help enhance the visual impression of a film and help create an atmosphere that fits the story being shown. However, too much camera movement or out-of-context can cause confusion or distraction for the viewer, which needs to be considered carefully in filmmaking. It is hoped that the dynamic camera movements applied in the film